Does water rights trading cause economic losses from agricultural water scarcity? Evidence from 264 Chinese cities - Jiajia Liu; Muhammad Umer; Jun Zhao; Qiang Li; Mei Qu (Agricultural Water Management)
China’s rapid economy growth has intensified the pressure on water resources, with agriculture being the largest consumer. Insufficient water in agriculture can constrain production and lead to significant economic losses. Water rights trading (WRT) is a key mechanism for reallocating water resources within and across water-scarce regions and industries. However, WRT often reallocates saved agricultural water to more economically productive sectors. A crucial consideration is whether this shift could lead to agricultural water scarcity, thus affecting agricultural production. This study examines whether WRT contributes to potential economic losses in agriculture. Using panel data from 264 Chinese cities from 2010 to 2020, we estimate the Agricultural Water Scarcity Risk (AWSR), which quantifies the economic loss caused by agricultural water scarcity, and analyze the impact of WRT on AWSR using the Spatial Difference-in-Differences method. Our findings reveal that: (1) WRT significantly alleviate the economic production loss due to agricultural water scarcity, with the results remaining robust after various tests; (2) WRT mitigates AWSR not only locally but also in neighboring cities; and (3) the policy’s effectiveness varies by region, being most effective in the Eastern region, followed by the Central region, and least in the Western region. This study highlights the importance of rational water resource management in agriculture and provides a foundation for developing strategies to mitigate agricultural water scarcity risk in high AWSR regions.